Analisis Efektifitas Penerapan Hak Upah Bagi Warga Binaan di Lapas Kelas I dan IIa Bandar Lampung - Athalla Rafhi Mahreza; A Irzal Fardiansyah; Maya Shafira (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Based on research conducted using normative and empirical juridical methods at Class I and IIA Correctional Institutions in Bandar Lampung, the implementation of wage rights for inmates participating in independence development programs as mandated by Law No. 22 of 2022 and Government Regulation No. 32 of 1999 shows that the wage distribution mechanism (50% incentive for inmates, 35% for development funds, and 15% to the state treasury) has been executed through collective labor agreements and an integrated bookkeeping system. The results indicate that over 70% of inmates actively participate in productive activities such as carpentry and handicrafts, with an average wage increase of 15% within one year due to innovations in waste-based craft products. However, productivity varies between activities (85% of target in woodworking versus 60% in sewing) due to raw material constraints, and wage disbursement is delayed by an average of 10 working days because of manual verification procedures and report synchronization. To optimize this system, it is recommended to increase the number of coaching and administrative staff, improve production facilities, digitize bookkeeping and inmate savings accounts, and diversify programs according to local market needs.